Effect of Vapor Heat Treatment on the Mortality of Bactrocera dorsalis (Diptera: Tephritidae) and the Quality of Mango cv. Arumanis - Tri Wulan Widya Lestari; Arman Wijonarko; Wayan Murdita; Suputa Suputa (Universitas Gadjah Mada, 2017)
Arumanis is a superior export variety mango from Indonesia. One inhibiting factor on the production of this fruit variety is the infestation of Bactrocera dorsalis (Diptera: Tephritidae) fruit fly. Vapor heat treatment was recommended by ISPM No. 28 of 2007 as an effective treatment in eradicating fruit flies. This research was aimed to find out the optimum temperature and the duration of vapor heat treatment on the mortality of egg and larvae of B. dorsalis. The experiment was conducted in the Laboratory of Vapor Heat Treatment, BBPOPT, Jatisari, from October 2016 to January 2017. The observed parameters were temperature, duration of treatment, mortality of egg and larvae of fruit fly, and fruit quality. The results showed that vapor heat treatment at 47°C for 40 minutes (min) was effective to reduce the number of eggs and larvae of B. dorsalis and had no negative impact on the fruit quality. IntisariBuah mangga varietas Arumanis merupakan varietas mangga ekspor unggulan Indonesia. Salah satu faktor pembatas produksi buah mangga varietas Arumanis adalah lalat buah B. dorsalis (Diptera: Tephritidae). Perlakuan uap panas direkomendasikan oleh ISPM Nomor 28 tahun 2007 sebagai tindakan perlakuan yang efektif dalam mengeradikasi lalat buah. Penelitian ini bertujuan untuk mengetahui suhu dan waktu optimum perlakuan uap panas terhadap mortalitas telur dan larva B. dorsalis pada buah mangga varietas Arumanis tanpa merusak kualitas buah. Penelitian dilaksanakan di Laboratorium Vapor Heat Treatment, BBPOPT, Jatisari, pada Oktober 2016 sampai dengan Januari 2017. Parameter yang diamati adalah suhu, lamanya waktu perlakuan, mortalitas telur dan larva lalat buah, dan kualitas buah. Hasil penelitian menunjukkan bahwa perlakuan uap panas pada suhu 47°C selama 40 menit terbukti efektif membunuh telur dan larva B. dorsalis dan tidak berdampak negatif terhadap kualitas buah.